Analisis Sistem Pengendalian Intern Persediaan Pada PT Wahana Subur Jaya - Lumbantoruan , Endang Feronika; Sihombing, Halomoan S.; Sidabutar, Rimbun C. D. (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
This research aims to find out and analyze the description of the internal control system for inventory of goods implemented at PT Wahana Subur Jaya. The type of research used in this research is qualitative research using comparative descriptive research methods. Data collection techniques are carried out by means of interviews and observations based on elements of internal control consisting of: 1) organizational structure that clearly separates functional responsibilities, 2) authorization system and recording procedures, 3) healthy practices, 4) high quality employees according to his responsibilities. From the research results, the internal inventory control system implemented by PT Wahana Subur Jaya is adequate. However, there are still some that do not comply with the elements of internal control according to the theory where there are several overlapping tasks in running the organization and the separation of functional responsibilities of the warehouse admin section.